Impact of Prosthesis-Patient Mismatch on 1-Year Outcomes after Transcatheter Aortic Valve Implantation: Meta-analysis of 71,106 Patients - Michel Pompeu Barros Oliveira Sá (Revista Brasileira de Cirurgia Cardiovascular/Brazilian Journal of Cardiovascular Surgery, 2019)
Objectives: This study sought to evaluate the impact of prosthesis-patient mismatch (PPM) on the risk of early-term mortality after transcatheter aortic valve implantation (TAVI).Methods: Databases (Medical Literature Analysis and Retrieval System Online MEDLINE, Excerpta Medica dataBASE EMBASE, Cochrane Controlled Trials Register CENTRAL/CCTR, ClinicalTrials.gov, Scientific Electronic Library Online SciELO, Latin American and Caribbean Literature on Health Sciences LILACS, and Google Scholar) were searched for studies published until February 2019. PPM after TAVI was defined as moderate if the indexed effective orifice area (iEOA) was between 0.85 cm2/m2 and 0.65 cm2/m2 and as severe if iEOA ≤ 0.65 cm2/m2.Results: The search yielded 1,092 studies for inclusion. Of these, 18 articles were analyzed, and their data extracted. The total number of patients included who underwent TAVI was 71,106. The incidence of PPM after TAVI was 36.3% (25,846 with PPM and 45,260 without PPM). One-year mortality was not increased in patients with any PPM (odds ratio OR 1.021, 95% confidence interval CI 0.979-1.065, P=0.338) neither in those with moderate PPM (OR 0.980, 95% CI 0.933-1.029, P=0.423). Severe PPM was separately associated with high risk (OR 1.109, 95% CI 1.041-1.181, P=0.001).Conclusion: The presence of severe PPM after TAVI increased early-term mortality. Although moderate PPM seemed harmless, the findings of this study cannot not rule out the possibility of it being detrimental, since there are other registries that did not address this issue yet.